1990
DOI: 10.1042/bj2650799
|View full text |Cite
|
Sign up to set email alerts
|

Cholera toxin modulation of angiotensin II-stimulated inositol phosphate production in cultured vascular smooth muscle cells

Abstract: Activation of phospholipase C by angiotensin II in vascular smooth muscle has been postulated to be mediated by an unidentified GTP-binding protein (G-protein). Using a permeabilized preparation of myo-[3H]inositol-labelled cultured vascular smooth muscle cells, we examined the ability of a non-hydrolysable analogue of GTP, guanosine 5'-[gamma-thio]triphosphate (GTP[S]), to stimulate inositol phosphate formation. GTP[S] (5 min exposure) stimulated inositol polyphosphate release by up to 3.8-fold in a dose-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

1990
1990
1998
1998

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 53 publications
0
23
1
Order By: Relevance
“…It has been shown that Gα q proteins mediate AngII-induced activation of phospholipase C-β " [2,5], and that Gα "$ couples the AT "A R to Ca# + mobilization in the portal vein [3]. Although immunoblotting analysis showed that α subunits of G i and G s are expressed to a similar extent as G q in VSMC [31], we have shown that AngII-induced IP $ generation is not sensitive to pertussis toxin and that activation of adenylate cyclase is not induced by AngII in VSMC [19]. Furthermore, in the study by Shirai et al [15], a peptide corresponding to amino acids 306-320 was a potent activator of Gα i and Gα o , in contrast to the observation that a similar peptide had no effect on basal GTPase activity in our system.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been shown that Gα q proteins mediate AngII-induced activation of phospholipase C-β " [2,5], and that Gα "$ couples the AT "A R to Ca# + mobilization in the portal vein [3]. Although immunoblotting analysis showed that α subunits of G i and G s are expressed to a similar extent as G q in VSMC [31], we have shown that AngII-induced IP $ generation is not sensitive to pertussis toxin and that activation of adenylate cyclase is not induced by AngII in VSMC [19]. Furthermore, in the study by Shirai et al [15], a peptide corresponding to amino acids 306-320 was a potent activator of Gα i and Gα o , in contrast to the observation that a similar peptide had no effect on basal GTPase activity in our system.…”
Section: Discussionmentioning
confidence: 92%
“…Using membrane fractions, [$H]AngII binding was measured as described previously [19], with minor modifications. Briefly, the binding reaction was initiated by the addition of the membrane suspension (100-200 µg of protein) to the binding assay buffer containing the appropriate concentration of [$H]AngII.…”
Section: [ 3 H]angii Binding Assaymentioning
confidence: 99%
“…To study the coupling of guanine nucleotide (GTP)-binding proteins to PLC, tritium-labeled VSM cells were permeabilized with saponin, 10 and phosphoinositol release determined in the absence and presence of a GTP analogue. In brief, [ 3 H]myoinositol-labeled VSM monolayers (35 mm) were washed with TBS.…”
Section: Angiotensin Ii-induced Phospholipase C Activitymentioning
confidence: 99%
“…11 Addition of the nonhydrolyzable guanosine-5'-O-(3-thiotriphosphate) (GTP-y-S) analogue to saponin-permeabilized VSM monolayers also resulted in inositol polyphosphate release. 10 These and synergism studies between GTP-y-S and Ang II demonstrated that the Ang H-induced PLC activation is coupled to a GTP-binding protein. 10 The occupied Ang II receptor also elicits activation of Na + -H + exchange in cultured VSM cells from SD rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation